The Sustainability of water abstraction from sand rivers as an adaptive strategy for climate change-induced poverty in the Nyamuzizi watershed in Mutoko District - Chidza, Petros (BUSE, 2024)
The battle against poverty is compounded by the world wide dearth of water spurred on by climate change. Moreover, the well-being of villagers in rural settings, like the Nyamuzizi Watershed in Mutoko District, who survive on water, particularly, drawn from sand rivers, have not been sufficiently documented.This study aimed to assess the sustainability of water abstraction from the Nyamuzizi sand river as an adaptation strategy to climate change-induced poverty. The objectives of the study were to examine the adequacy of water sources within the Watershed, evaluate the alleviation of poverty through socioeconomic benefits derived from the sand river, analyse the impact of water scarcity on land use and land cover patterns, and determine the effectiveness of governance frameworks in the management of water from Nyamuzizi River A mixed method study, which included a focus group interview, open-ended individual interviews, field observation, documentary research, GIS and Remote Sensing were employed. Convenience sampling was used to select Nyahondo-Marira Ward 23 for data collection from a population of wards within the watershed of Nyamuzizi River. Officials who were interviewed were selected using a purposive sampling method. The study uncovered significant inadequacies in water resources within the area, undermining their capacity to support socio-economic development initiatives aimed at poverty alleviation within the ward. Furthermore, the sustainability of water abstraction from sand aquifers in the Nyamuzizi River is jeopardized by widespread land use/land cover changes. These changes, coupled with an ineffective local water governance framework, pose serious threats to the long-term availability and usability of water resources in the region. In conclusion, the study recommends a hydrogeological study of the watershed, the establishment of irrigated systems on plots situated away from the river basin, as well as strengthening of sand river governance frameworks. These recommendations aim to mitigate the impact of water scarcity and land degradation, enhance agricultural productivity, and promote sustainable land and water management practices in the Nyamuzizi Watershed